2017
DOI: 10.3892/or.2017.5831
|View full text |Cite
|
Sign up to set email alerts
|

miR-374 mediates the malignant transformation of gastric cancer-associated mesenchymal stem cells in an experimental rat model

Abstract: Mesenchymal stem cells (MSCs) are a critical component of the tumor microenvironment. Upon distinct pathological stimulus, MSCs show phenotypic and functional changes. Gastric cancer is one of the leading causes of cancer-related deaths worldwide. The roles and mechanisms of MSCs in gastric cancer have not been well characterized. In the present study, we investigated the roles of MSCs in the malignant transformation from gastritis to gastric cancer using an N-methyl-N'-nitro-N-nitrosoguanidine (MNNG)-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The diagnostic value of serum miR-374a-5p was higher than traditional diagnostic markers, such as alpha fetoprotein (AFP) or carcino-embryonic antigen (CEA) 16 . In addition, we found that the expression of miR-374a-5p was increased in the serum of patients with pre-cancerous gastric lesions, which was consistent with our previous study showing that the expression of miR-374a-5p was also increased in the serum of MNNG-exposed rats with atypical hyperplasia in gastric tissues 4 . Thus, miR-374a-5p may serve as a potential biomarker for the early diagnosis of gastric cancer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The diagnostic value of serum miR-374a-5p was higher than traditional diagnostic markers, such as alpha fetoprotein (AFP) or carcino-embryonic antigen (CEA) 16 . In addition, we found that the expression of miR-374a-5p was increased in the serum of patients with pre-cancerous gastric lesions, which was consistent with our previous study showing that the expression of miR-374a-5p was also increased in the serum of MNNG-exposed rats with atypical hyperplasia in gastric tissues 4 . Thus, miR-374a-5p may serve as a potential biomarker for the early diagnosis of gastric cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Our recent study revealed that miR-374 promoted the proliferation and migration of transformed mesenchymal stem cells (MSCs) by regulating the Wnt5a/β-catenin signaling pathway, which, to a certain extent, contributed to the transformation of rat bone marrow-derived MSCs to the K3 tumor cell line 3 . In addition, the upregulation of miR-374 in MSCs from the gastritis tissues of MNNG (N-methyl-N′-nitro-N-nitrosoguanidine)-exposed rats could increase their proliferation and migration abilities 4 . Other studies showed that miR-374-5p overexpression promoted the proliferation, migration, and invasion of gastric cancer cells by targeting SRCIN1 and RECK genes 5, 6.…”
Section: Introductionmentioning
confidence: 98%
“…Xie J showed that the expression of miR‐374b‐5p was up‐regulated and conducive to gastric cancer cell invasion and metastasis via inhibiting the expression of RECK . Ji et al presented that the up‐regulation of miR‐374 mediated the malignant transformation of gastric cancer‐associated mesenchymal stem cells and represented a novel avenue for gastric cancer therapy with an experimental rat model. In the same year, Sierzega et al found that miR‐374 was abnormally expressed in the primary tissue of gastric cancer, but its expression was not changed in the serum of GC patients …”
Section: The Role Of Mir‐374 In Tumorigenesismentioning
confidence: 99%
“…It has been reported that MSCs can be recruited to tumors and participate in the formation of the tumor stroma [ 43 47 ]. Recent studies have shown that MSCs can undergo malignant transformation when they are cultured for a long period of time or in a tumor-like environment, although the underlying mechanism remains unknown [ 10 , 30 , 48 , 49 ]. In this study, we induced MSCs to undergo malignant transformation by indirectly coculturing them with C6 glioma cells.…”
Section: Discussionmentioning
confidence: 99%